Draft Principles and Guidelines for Integrating: Ecosystem-based Approaches to Adaptation in Project and Policy Design - Andrade, Angela; Córdoba, Rocío; Dave, Radhika; Girot, Pascal; Herrara F., Bernal; Munroe, Robert; Oglethorpe, Judy; Paaby, Pía; Pramova, Emilia; Watson, James; Vergara, Walter (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2022)
This document proposes a series of draft principles and guidelines that were produced at a workshop with participation of its authors in June 2011, with the aim to serve as a foundation for planning ecosystem-based approaches to adaptation. The principles are intended to be used by decision makers in national policy in national, territorial and sector planning initiatives, in financial planning, and in project and research design. Hence, the draft set of guidelines is meant to support best-practices for the design and implementation of ecosystem-based approaches to adaptation.